The Impact of Occupational Health and Safety Practices on Job Performance of Operational Level Employees: A Study in the Construction Industry, Sri Lanka - H.P.N.I. Kumarasinghe; H.K.T. Dilan (International Journal of Management, Accounting and Economics, 2022)
In the modern developing business world, a significant increase in Health and Safety Practices can be identified. Occupational accidents in factories and working sites make substantial challenges to survive. Hence, this study aims to determine the impact of occupational health and safety practices on the job performance of operational level employees in the construction industry, Sri Lanka. The study was carried out among a sample of 100 operational level employees in selected construction sites in Sri Lanka. The study provided a comprehensive questionnaire to assess the impact of health and safety on the job performance of the operational level employees by using random sampling technique. Secondary data were used from company past data and information, web site, journals, and subject-related books such as company health and safety procedures, health and safety training, and accident records. Data analysis was done by using SPSS. The study found a positive impact of occupational health and safety practices on the job performance of operational level employees in the construction industry.